Four Studies of Executives Helping Employees Align Their Actions and Values - Friedman, Stewart D. (Senate Hall Academic Publishing, 2005)
What does it take for business leaders to integrate the different domains of their lives (work, home, community and self) and what must they do to ensure that the people in their organizations are able to do the same? These are the questions that were taken up in innovative ways by the “work/life movement” as it began to find its voice about two decades ago. At the University of Pennsylvania’s Wharton School, the Work/Life Integration Project convened a group of business school faculty and business leaders to see if we could find some answers. And we did. Over the past 15 years we have met on five occasions, each time focusing our efforts on generating useful knowledge; ideas for action that people in organizations might use to improve performance by integrating work and personal life.